DNA barcoding of blackflies (Diptera: Simuliidae) as a tool for species identification and detection of hidden diversity in the eastern regions of Spain - Garza-Hernandez, Javier Alfonso (2018)
Background: Blackflies have negative impact on public and animal health due to the haematophagous habit of females. In recent times, in some regions in Spain, blackfly outbreaks are becoming more and more frequent, threatening the public health. However, there is still a paucity of data concerning the Spanish blackfly fauna. Correct identification of species is of paramount importance in order to provide correct information on species distribution, biology and behaviour, so that control measures could be implemented appropriately. Methods: Blackflies specimens (larvae, pupae, reared adults and biting females) were collected in the period 2015–2017 in and near rivers and streams from different regions in Spain. A modified Hotshot technique was used for the DNA extraction and the cox1 DNA barcoding region of the cytochrome c oxidase subunit 1 was sequenced from the specimens collected. Results: In total, we collected 239 specimens representing 22 species. Of these, six species are new records for the Aragón region: P. tomosvaryi, S. bertrandi, S. galloprovinciale, S. lineatum, S. rubzovianum and S. xanthinum. Cox1 DNA barcode sequences for 21 species were recovered, including four species of the genus Prosimulium and 17 species of the genus Simulium [Boophthora (1 species), Eusimulium (1 species), Nevermannia (4 species), Simulium (s.s.) (6 species), Trichodagmia (1 species) and Wilhelmia (4 species)]. For the first time the complete DNA barcodes for five species (P. tomosvaryi, S. carthusiense, S. brevidens, S. monticola and S. sergenti) were registered. Most of the specimens belonging to the same recognized species were clustered together in the neighbour-joining tree, except for S. argyreatum, S. monticola and S. variegatum. The overall genetic distance in the dataset was 0.14%. The average of the intraspecific genetic divergence within the different taxa was 1.47% (0.05–3.96%). In contrast, the interspecific divergence varied between 2.50–22.0%. Conclusions: In this study we assessed the use of the cox1 DNA barcoding region for the identification of species of blackflies in Spain. Our results showed that combining DNA barcoding with morphology enhanced our taxonomic rationale in identifying the blackflies in the country.